Coupling transient mixed lubrication and wear for journal bearing modeling. (October 2019) - Xiang, Guo; Han, Yanfeng; Wang, Jiaxu; Wang, Jiefu; Ni, Xiaokang
Abstract: A transient Mixed Lubrication-Wear coupling model (MLW coupling model) is developed to investigate the mixed lubrication and wear performances of journal bearings, and a wear experiment for journal bearing is performed to support the validity of the developed numerical model. In the coupling numerical model, the transient interaction between the behaviour of mixed lubrication and wear is considered by incorporating the wear depth distribution, which is determined by the developed friction fatigue wear model, into the film gap equation. The evolutions of the worn surface profile, wear rate, fluid pressure and asperity contact pressure over operating time are calculated by the developed numerical model. The simulated results demonstrate that the transient wear process affects the distribution trend of lubrication performances significantly, and a worn surface profile may exist that provides an optimal tribology performance of journal bearings. The simulated results also demonstrate that there are two wear stages, identified by initial and steady wear stage, of journal bearings under mixed lubrication condition. Furthermore, the effects of the input parameters, including the radius clearance( C ), surface roughness ( σ ), asperity curvature radius ( β ) and boundary friction coefficient( μ c ), on the predicted mixed lubrication and wear performance are evaluated. Highlights: A transient Mixed Lubrication-Wear coupling model (MLW coupling model) for journal bearings is developed. The effects of transient mixed lubrication performance on the wear are considered by a developed fatigue wear model. The evolution of the lubrication and wear performance over operating time is determined.